When Knowledge is Power: Three Models of Change in International Organ izations - Haas, Ernst B. (University of California Press, 1991)
Do governments seeking to collaborate in such international organizati ons as the United Nations and the World Bank ever learn to improve the performance of those organizations? Can international organizations b e improved by a deliberate institutional design that reflects lessons learned in peacekeeping, the protection of human rights, and environme ntally sound economic development? In this incisive work, Ernst Haas e xamines these and other issues to delineate the conditions under which organizations change their methods for defining problems. Haas conten ds that international organizations change most effectively when they are able to redefine the causes underlying the problems to be addresse d. He shows that such self-reflection is possible when the expert-gene rated knowledge about the problems can be made to mesh with the intere sts of hegemonic coalitions of member governments. But usually efforts to change organizations begin as adaptive practices that owe little t o a systematic questioning of past behavior. Often organizations adapt and survive without fully satisfying most of their members, as has be en the case with the United Nations since 1970. When Knowledge Is Powe r is a wide-ranging work that will elicit interest from political scie ntists, organization theorists, bureaucrats, and students of managemen t and international administration.